Ventilator-Associated Pneumonia: Diagnosis, Prevention, Treatment (State-of-the-Art of the Problem) - I. N. Yegorova; A. V. Vlasenko; V. V. Moroz; V. N. Yakovlev; V. G. Alekseyev (Общая реаниматология, 2010)
By analyzing the data available in the Russian and foreign literature and their many years’ experience, the authors review the state-of-the-art of the problem associated with ventilator-associated pneumonia in intensive care units. The etiology, epidemiology, and pathogenesis of ventilator-associated pneumonia, the possibilities and limitations of its prevention and diagnostic methods, successes and difficulties and treatment of this pathology are described in detail.